Importance of Cardiovascular Magnetic Resonance Applied to Congenital Heart Diseases in Pediatric Age: A Narrative Review - Sara Moscatelli; Alice Pozza; Isabella Leo; Jessica Ielapi; Alessandra Scatteia; Sofia Piana; Annachiara Cavaliere; Elena Reffo; Giovanni Di Salvo (Children, 2024)
Congenital heart diseases (CHDs) represent a heterogeneous group of congenital defects, with high prevalence worldwide. Non-invasive imaging is essential to guide medical and surgical planning, to follow the patient over time in the evolution of the disease, and to reveal potential complications of the chosen treatment. The application of cardiac magnetic resonance imaging (CMRI) in this population allows for obtaining detailed information on the defects without the necessity of ionizing radiations. This review emphasizes the central role of CMR in the overall assessment of CHDs, considering also the limitations and challenges of this imaging technique. CMR, with the application of two-dimensional (2D) and tri-dimensional (3D) steady-state free precession (SSFP), permits the obtaining of very detailed and accurate images about the cardiac anatomy, global function, and volumes’ chambers, giving essential information in the intervention planning and optimal awareness of the postoperative anatomy. Nevertheless, CMR supplies tissue characterization, identifying the presence of fat, fibrosis, or oedema in the myocardial tissue. Using a contrast agent for angiography sequences or 2D/four-dimensional (4D) flows offers information about the vascular, valvular blood flow, and, in general, the cardiovascular system hemodynamics. Furthermore, 3D SSFP CMR acquisitions allow the identification of coronary artery abnormalities as an alternative to invasive angiography and cardiovascular computed tomography (CCT). However, CMR requires expertise in CHDs, and it can be contraindicated in patients with non-conditional devices. Furthermore, its relatively longer acquisition time and the necessity of breath-holding may limit its use, particularly in children under eight years old, sometimes requiring anesthesia. The purpose of this review is to elucidate the application of CMR during the pediatric age.